PREDICTION OF PLANET 9 DETECTION USING MICROLENSING METHOD - Zahra, Fatimah
Up to this date, the existence of Planet 9 which is hypothesized to has caused orbital anomalies to 14 distant Kuiper Belt Objects (KBOs) has not been directly detected. Likely, this is caused by how faint Planet 9 is, with visual magnitude approximated around 20 < V < 25. One of the effective methods known for detecting such faint objects such as a planet is microlensing. Assuming that Planet 9 has mass between 5 M? < m < 10 M? and semi-major axis of 400 au < a < 800 au, microlensing parameters and orbital simulations for Planet 9 candidates were calculated. Thus, the aim of this work is determining the likelihood and probability of detecting Planet 9 through microlensing events. The results indicate that with Einstein radius in the range of 8 - 12 ?as, Planet 9 candidates could cause microlensing events with source stars brightness change ?m of 2.9 - 5.1 magnitudes and microlensing timescale tE ranging around 20 - 71 minutes. With current technology, there is a possibility that Planet 9 could be detected through microlensing events. However, no microlensing event by Planet 9 has yet been found that might occur within 12 years, in sky region < 90° and 30° < ? < 45°. There are not even a single star from GAIA dr-3 data archive that are sufficiently close enough to Planet 9 candidates, such that the distance between the stars and Planet 9 candidates are smaller than the Einstein radius.